[PS 08-40] ASSOCIATION BETWEEN eGFR DECLINE AND HIGH ROOM TEMPERATURE DURING SUMMER REVEALED BY AUTOMATED HOME BLOOD PRESSURE TELEMONITORING. (September 2016) - Yatabe, Junichi; Yatabe, Midori; Bokuda, Kanako; Watanabe, Daisuke; Ando, Takashi; Morimoto, Satoshi; Watanabe, Tsuyoshi; Ichihara, Atsushi
Abstract : Objective: Self-measurement of blood pressure at home is beneficial to assess its seasonal variability. However, the association between room temperature at the time of blood pressure measurement and renal function has not been studied. Design and Method: A commercially-available blood pressure monitor equipped with thermometer (HEM-7251G, OMRON) was used. Twenty-four patients with essential hypertension measured their blood pressure at home for more than a year. Estimated glomerular filtration ratio (e-GFR) was calculated by modified estimating equation for Japanese. Results: Mean observation period was 610 days. Mean room temperature at the time of blood pressure measurement was 17.2 ± 5.4°C, average of personal maximum room temperature (range) was 29.9°C (23–37) and minimum room temperature was 6.0°C (0–16). Home blood pressure showed seasonal variation and there was a strong and significant association between blood pressure and room temperature (P < 0.01) independently of age and sex. Room temperature positively associated with standard deviation of eGFR (R = 0.6, P < 0.01). Annual decline in eGFR was significantly increased with maximum room temperature (R = -0.5, P < 0.05) while there was no association between renal function and minimum room temperature. Conclusions: Impaired renal function was observed in summer. Degree of variation in room temperature correlated with the degree of variations in pulse rate and eGFR. An appropriate air conditioning to maintain ambient room temperature may benefit renal prognosis.